2016
DOI: 10.1152/ajplung.00305.2015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypersensitivity pneumonitis caused by Saccharopolyspora rectivirgula is not associated with a switch to a Th2 response

Abstract: Andrews K, Ghosh MC, Schwingshackl A, Rapalo G, Luellen C, Waters CM, Fitzpatrick EA. Chronic hypersensitivity pneumonitis caused by Saccharopolyspora rectivirgula is not associated with a switch to a Th2 response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Experimental models of HP show that IL-17A is involved in lung inflammation induced by Saccharopolyspora rectivirgula (7)(8)(9)(10)(11), pigeon dropping extract (PDE) (12), and Stachybotrys chartarum (13). IL-17A is involved in a variety of immunological responses, such as enhanced production of proinflammatory cytokines and chemokines and direct immune cell recruitment (14,15).…”
mentioning
confidence: 99%
“…Experimental models of HP show that IL-17A is involved in lung inflammation induced by Saccharopolyspora rectivirgula (7)(8)(9)(10)(11), pigeon dropping extract (PDE) (12), and Stachybotrys chartarum (13). IL-17A is involved in a variety of immunological responses, such as enhanced production of proinflammatory cytokines and chemokines and direct immune cell recruitment (14,15).…”
mentioning
confidence: 99%
“…In contrast to these findings in our healthy mold-exposed cohort of agricultural workers, we and others previously reported that patients with Aspergillus- associated hypersensitivity diseases, such as ABPA, display strongly elevated Th17 cytokine responses to A. fumigatus antigens [ 12 , 28 ]. Although important in the initial stage of fungal clearance [ 29 , 30 , 31 , 32 ], enhanced Th17-cell activation has been associated with Aspergillus airway colonization and fungal persistence and is considered a driving factor in the establishment of hypersensitivity pneumonitis, a potential complication of chronic occupational mold exposure [ 28 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fungi such as Aspergillus spp. have also been epidemiologically and serologically linked to HP and a more complex immune response that includes T H 2 cell activation in more severe and chronic forms of HP [51,52]. Notably, inclusion of fungi and viable organisms of any type in models of HP has been lacking thus far.…”
Section: Discussionmentioning
confidence: 99%